Roots Bioassay of Upland Rice Varieties on Several Soil Moisture Gradients - Syarifa Mayly; A. Rauf; Chairani Hanum; Hamidah Hanum (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Water availability is a major factor affecting rice production especially in upland.  The Production of upland rice is low because of the low of  water availability in upland.  Roots play an important role in upland rice adaptation to drought conditions. This study aimed to identify the characteristic of upland rice variety root development under  soil moisture gradients. This study use  randomized  factorial design consisting of 2 factors and 3 replicate.  Factor I : 12 upland rice variety, ie: Silumut, Batutegi, Limboto, Situpatenggang, Situbagendit, Towuti, Cirata,  Danau Gaung, Gajah Mungkur, Inpago 4, Inpago 5, Inpago 6. Factor II :  gradien of soil moisture level, ie: 20 %, 40 %, 60 %, 80 % field capacity. The Result of research indicate all the upland rice variety were classified tolerance based on relative value of root leght. The highest root lenght and the heaviest root dry matter were generally from combination uplandrice varieties with 60 80 % field capacity except Inpago 4 and Situbagendit showed  the highest root lenght at 20 % field capacity and combination The heaviest root dry matter at 40 %were Inpago 4 and Jatiluhur generally from characteristic of  root gro field capacity